If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3s + 8 = -10 Reorder the terms: 8 + 3s = -10 Solving 8 + 3s = -10 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 3s = -10 + -8 Combine like terms: 8 + -8 = 0 0 + 3s = -10 + -8 3s = -10 + -8 Combine like terms: -10 + -8 = -18 3s = -18 Divide each side by '3'. s = -6 Simplifying s = -6
| -5(2-5k)-6=134 | | 408.33=95-2x | | 3t+4=500+t | | 4(x-5)=12+x+x | | -4(x-6)-7=39 | | 16=4w+2w?2 | | -6(1+7n)=-132 | | 9/11=a | | 2x+7y=1000 | | 5(x-6)+9=43 | | -2f/3=2 | | 5(6-8x)=-130 | | -3(x-7)=17 | | 2y-5=y-2 | | 2/7=r | | 14x+70=7 | | 2(x+11)=54 | | (x^3)+(5x^2)-9x-45=0 | | 3b=-9 | | 3000-120x=15000 | | 93-(4m-8)=53 | | 2(3c)=36 | | f=(12)60-2/3r | | X*2+x*2=-14-3 | | -200x-2500=5100 | | -124=-4v-2(6+6v) | | -4x-18=73 | | y=x/2-13^3 | | 5-w+11=51 | | 7+7(7n-8)=98 | | 6x-(3x+7)=27 | | 2x+29=300 |